Economic cooperation in the Shanghai Cooperation Organization analysis - V. V. Pylypenko (Вестник университета)
The Shanghai Cooperation Organization (hereinafter – SCO) was established in 2001 and since then has expanded its membership and scope of activities. The purpose of the study is to analyze the economic aspects of cooperation within the SCO and the existing problems hindering further economic interaction, as well as to identify promising development areas. To achieve this goal the author used general scientific and historical methods that allow us to analyze and evaluate information such as generalization, data analysis and synthesis, method of logical and comparative analysis, comparison and contrast. The current state and prospects of economic cooperation within the SCO have been analyzed. Trade, investments, infrastructure projects, energy, and other areas of interaction have been considered. The SCO economic agenda is aimed at increasing regional trade, improving market access, promoting regional ties, and consolidating the economic potential of member states. However, unresolved territorial disputes between China, India and Pakistan impede the deepening of economic ties. In turn, the recent accession of Iran opens up new opportunities for trade and transportation corridors. Prospects for an SCO free trade zone, joint infrastructure projects, financial cooperation, and high-tech partnerships have been highlighted as strategic goals. In general, further economic integration is in line with the member states’ national interests. Eliminating internal tensions and developing effective communication mechanisms will help strengthen the SCO as an organization and realize its economic potential.